Building an Antibiotic Stewardship Program: An Interactive Teaching Module for Medical Students - Jennifer L. Hsu (Association of American Medical Colleges, 2018)
Introduction Given the increasing importance of antibiotic stewardship, an understanding of the basic tenets of antibiotic prescribing is critical for all medical students. This engaged learning module focuses on terminology and foundational concepts in antibiotic stewardship while assisting learners with application in their early clinical practice. Methods This module was developed for third-year internal medicine clerkship students at the University of South Dakota, Sanford School of Medicine. The students participated in an introductory discussion of the harms of antibiotic overuse in a large-group format, followed by small-group work to develop a miniature antibiotic stewardship program. Upon completion of the small-group portion, the large group reconvened to share antibiotic stewardship strategies and to complete the session with additional training regarding individual provider and system-level antibiotic stewardship strategies. Results Approximately 150 students have participated in this module. Through use of the module, students have been highly engaged in identifying antibiotic stewardship interventions in their early practice and creating potential solutions. Themes identified during analysis of one-minute paper responses demonstrated student learning around the rationale for antibiotic stewardship programs, implementation strategies, and patient education. Discussion This module was primarily developed for medical students, but it could easily be adapted for use with learners of varying levels. Additionally, it could be implemented as an interprofessional exercise to leverage the expertise of trainees in pharmacy and nursing.